Internet connectivity disruption in Paraguay (Paraguay) - Voidly (2026)
CRITICAL severity disruption detected in Paraguay. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: PY-2026-0017
Keywords: internet disruption; PY; disruption; critical